2008
DOI: 10.1159/000117799
|View full text |Cite
|
Sign up to set email alerts
|

Cemented and Cementless Total Hip Replacement

Abstract: Objective: In this study we present the results of a series of cemented Exeter and cementless Zweymüller implants. Subject and Methods: Eighty-seven cemented and 95 cementless hip replacements for different hip pathologies were followed for an average period of 36 months for cementless and 60 months for cemented cases. Clinical results were calculated using the Merle d’Aubigne score. The orientation of the prosthetic components and the fixation of the cup and stem were analyzed. The clinical and radiological r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Following detailed evaluation of full texts, 12 articles were excluded. The remaining 22 articles based on 11 distinct observational cohort studies and 4 RCTs met the inclusion criteria and were included in the review (Figure 1; Table 1) [10,12,13,14,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41].…”
Section: Resultsmentioning
confidence: 99%
“…Following detailed evaluation of full texts, 12 articles were excluded. The remaining 22 articles based on 11 distinct observational cohort studies and 4 RCTs met the inclusion criteria and were included in the review (Figure 1; Table 1) [10,12,13,14,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41].…”
Section: Resultsmentioning
confidence: 99%
“…Pospula et al observed a higher loosening rate if a cemented cup was used in comparison to cementless cup fixation [24]. Based on the results we present here, however, it is more likely that the position of the hip rotation center was the reason for the earlier loosening of cemented cups.…”
Section: Discussionmentioning
confidence: 40%
“…Several published reports on the preliminary results of total hip arthroplasty demonstrated that a superior and lateral position of the hip rotation center can lead to early aseptic loosening [9,10,23,24]. All of these reports, excepting the study from Pospula et al, observed patients with cemented prostheses.…”
Section: Discussionmentioning
confidence: 99%